Managing Students’ Creativity in Music Education – The Mediating Role of Frustration Tolerance and Moderating Role of Emotion Regulation - Wang, Lei; Jiang, Na (Frontiers in Psychology, 2022)
AI era challenges the use and functions of emotion in college students and the students` college life is often experienced as an emotional rollercoaster, negative and positive emotion can affect the emotional outcomes, but we know very little about how students can ride it most effectively to increase their creativity. We introduce frustration tolerance as a mediator and emotion regulation as a moderator to investigate the mechanism of creativity improvement under negative emotion. Drawing on a sample of 283 students from professional music colleges or music major in normal universities, we find that negative emotion are generally associated with a lower creativity, while frustration tolerance can mediate the relationship between negative emotion and creativity, but these effects depend on the emotion regulation. Cognitive reappraisal exerts a negative effect on the relationship between negative emotion and creativity, while expressive suppression has the opposite effect. Our study contributes to the literatures on student`s emotions and creativity in music education and to the emotion regulation literature.